Analisis Hukum Keluarga Terhadap Dampak Judi Online Dalam Keharmonisan Rumah Tangga Di Kota Pontianak - toni_ toni (LP3M INSTITUT KH YAZID KARIMULLAH, 2024)
This study aims to analyze the impact of online gambling on household harmony in Pontianak City and review how the family law perspective views the problem. Online gambling, as a form of modern gambling, has caused various social and legal problems, including disruption of economic, psychological, and emotional stability in the household. This study uses a juridical-sociological approach, this study examines primary data in the form of interviews with affected families and law enforcement officers, and secondary data from legal literature and laws and regulations. The results of the study indicate that the involvement of one family member in online gambling activities significantly affects household harmony, such as increased conflict, divorce, and loss of trust between couples. From a family law perspective, this action is a violation of the responsibility and obligation to maintain family welfare as regulated in Law Number 1 of 1974 concerning Marriage. The factors behind gambling are internal and external factors. Internal factors because they come from self-confidence that expects victory from gambling because it is always overshadowed by an increasing curiosity to hope for a victory. External factors of economic problems and several other factors such as environmental factors that make them interested in gambling.